2021
DOI: 10.3389/fcvm.2021.676267
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast-Derived Exosome Induce Cardiac Endothelial Cell Dysfunction

Abstract: Background: Endothelial cells (ECs) play a critical role in the maintenance of vascular homeostasis and in heart function. It was shown that activated fibroblast-derived exosomes impair cardiomyocyte function in hypertrophic heart, but their effect on ECs is not yet clear. Thus, we hypothesized that activated cardiac fibroblast-derived exosomes (FB-Exo) mediate EC dysfunction, and therefore modulation of FB-exosomal contents may improve endothelial function.Methods and Results: Exosomes were isolated from card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…However, first in vitro approaches revealed that fibroblast not only secrete paracrine factors, but also release microRNA‐loaded exosomes to communicate with endothelial cells. In a profibrotic setting, it was shown that mouse cardiac endothelial cell function is impaired when cultured with exosomes that were isolated from TGFβ‐pretreated fibroblasts [122]. These findings are of potential interest since the up‐take of fibroblast‐derived miR in endothelial cells might change their phenotype toward mesenchymal cells.…”
Section: Communication Between Fibroblasts and Endothelial Cellsmentioning
confidence: 99%
“…However, first in vitro approaches revealed that fibroblast not only secrete paracrine factors, but also release microRNA‐loaded exosomes to communicate with endothelial cells. In a profibrotic setting, it was shown that mouse cardiac endothelial cell function is impaired when cultured with exosomes that were isolated from TGFβ‐pretreated fibroblasts [122]. These findings are of potential interest since the up‐take of fibroblast‐derived miR in endothelial cells might change their phenotype toward mesenchymal cells.…”
Section: Communication Between Fibroblasts and Endothelial Cellsmentioning
confidence: 99%
“…As EVs play role in cardioprotective mechanisms [ 27 ], we expected that HeC modulate the release of mEVs by NRCFs. Here, we found that HeC tended to decrease the number of mEVs released by NRCFs, the cardioprotective role of which could be explained by a recent study which shown that EVs secreted by activated CFs impaired endothelial functions [ 39 ].…”
Section: Discussionmentioning
confidence: 89%
“…According to NYHA classification, a study found that the more severe the HF, the higher the MMP-9 level [ 33 ]. VEGF is an important growth factor, which is involved in many processes of human growth and development, such as angiogenesis and osteogenesis, and plays an important role in maintaining vascular homeostasis and normal cardiac function [ 34 ]. The level of VEGFA can regulate the HIF-1/VEGFA signaling pathway and reverse hypoxia-induced myocardial injury by regulating the level of HMOX1 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%